Development of Skills for The Employability of New Professionals: A Perspective of The Practitioners in A Peruvian Public Institution - Elizabeth Emperatriz GARCÍA-SALIRROSAS; Anggie Zullyt AÑI RAMOS; Isabel ALVIS HERNANDEZ (Communications of International Proceedings, 2021)
The present study aimed to determine the development of skills for employability that young people have through the development of their pre-professional practices. For this, a study with a quantitative approach was carried out, collecting information from 218 practitioners from a public institution. The study of 5 dimensions was carried out: Occupational experience, Anticipation and optimization, Personal flexibility, Corporate sense and balance. The results show that 100% of young people feel that they have managed to develop their skills at a high level and feel prepared to enter the labor field, however, they consider that their work efforts are not proportional to what they get in return during their practices, that is why it is recommended that the programs should be carried out taking into account that they are basically training programs and be careful with the excess of activities that can be given to the practitioners.
Keywords: Employability; Young professionals; Job skills.